Infecções de corrente sanguínea relacionada e associada a cateteres vasculares centrais em neonatos críticos: etiologia, patogenia e fatores de risco - Urzedo, Jane Eire (2013)
Nosocomial infections (NIs) are responsible for significant rates of morbidity and mortality in Neonatal Intensive Care Units (NICUs), even resulting in prolonged hospitalization and increased hospital costs. The bloodstream infections associated with catheters (CA-BSI) are frequent, often fatal and costly, particularly in the group of newborns with low weight units in developing countries like Brazil. The aim of the study was to determine the incidence of neonatal hospital BSI, as well as the etiology and antimicrobial resistance profile, analyze the characteristics of infected neonates and to investigate the pathogenesis of these infections in newborns admitted to the NICU critics of the Clinical Hospital of the Federal University of Uberlândia-MG. The prospective cohort study was conducted between January/2011 and December/2011. In the total, 264 neonates were investigated using CVC through surveillance \"National Healthcare Safety Network.\" Blood cultures were performed using an automated method (BACTEC / VITEK ®) in the microbiology laboratory of the hospital. Additionally, cultures were performed nasal mucosa, intestinal, skin at the insertion site, and barrel tip CVC. The incidence of infection of the bloodstream associated with and related to the CVC was 16.7 and 4.4 / CVC 1000 days, respectively. The incidence of BSI associated with the use of CVC was higher (32%) in neonates weighing 1001-1500g. As in BSI associated with CVC, the PICC was responsible for the higher frequency (78.5%) of CVC-related BSI, especially also for weight range of 1001 to 1500 g. The main agent of sepsis with microbiological diagnosis was Staphylococcus epidermidis (51%), followed by S. aureus (10.6%), Gram-negative bacilli (21.27%), Candida albicans (7.54%) and Candida tropicalis (2.12%). Of the 43 neonates with BSI, 24 showed some correlation with the sites: skin, cannon tip of CVC and intestine differing routes of acquisition likely to BSI in intraluminal, extraluminal, indeterminate and likely intestinal translocation. Altogether, 96 neonates were collected in sites nostril and perianal region. Of these, about 36.7% were colonized in the nostril and 56.0% in the intestine, at least one of the collections. The gram positive were more frequent in the nostril, with the main representative Streptococcus epidermis (77.3%). Perianal the gram negative bacilli predominated 48.6%, followed by 35.8% Yeasts . The use of total parenteral nutrition, use of PICC and CVC type of CVC usage time ≥ 16 days were statistically independent risk factors for the development of BSI. A incidence rate of neonatal hospital BSI was 25.3%, being sepsis the main infectious syndrome.